Indicators and Models of Analysis of the Financial Situation of a Company - Galabov, Marin (Research Papers, 2007)
Studios are the places where possibilities for analyzing different aspects of companies’ financial standing are represented by means of certain indexes. Those are classified as aspects of the so called “effect – expenses or resources” type and “assets and/or capitals” one. Besides some models for analyzing companies’ financial standing are also introduced there.The Studio has the following structure – an introduction; a first part consisting of indicators for analyzing the aspects of financial standing of one of the types mentioned above; a second part for the same indicators but of the other type; a third part where models for financial standing analyzing is represented and a conclusion.Studios could be helpful either to finance analysis experts or to those who study in the same field. The accent in such Studios is mainly on the indexes and models which could be used to analyze finance standing. Practically, the reason companies’ finance management do analysis is to optimize the finance standing of their companies.